“Induced Electron Transfer” in Silk Cocoon Derived N-Doped Reduced Graphene Oxide-Mo-Li-S Electrode - Jangir, Himanshi; Bhardwaj, Amarjeet; Ramkumar, Janakarajan; Sarkar, Sabyasachi; Das, Mainak (Frontiers in Materials, 2019)
Developing 'carbon lithium sulfide composite (C-Li2S)' cathode is a promising strategy for Li-S battery. Quite interestingly, when Li and S are caged in a heavily nitrogen-doped reduced graphene oxide (NDRGO) matrix derived from Tassar silk cocoon, the composite (NDRGO-Li-S) electrode behaves like a supercapacitor. In this work, we first optimized the concentrations of sulfur and then introduced molybdenum in the NDRGO matrix to develop a stable NDRGO-Mo-Li-2S (where 2 stands for 2M) composite electrode. The electrode design process utilized the concepts of ‘embedded redox couples' and ‘induced electron transfer’; a putative strategy to alter internal electron-shuttling kinetics for applications in various charge storage devices; where a time of electron-shuttling is the key. In NDRGO-Mo-Li-2S composite the charge transport occurs via ‘induced electron transfer’, where Li+, is an external oxidant, provoking the inter atom electron transfer between Mo(VI), the internal oxidant, and S(-II), the internal reductant in Mo-S redox couple. This redox reaction is reversed using NDRGO, an external reductant inducing inter atom electron flow across (Mo(V)–(S2)) to complete the starting to product and back cycle. Such a redox cycle is competent for the flow of electrons in a lasting charge storage material through this unique bio-inorganic hybrid approach.